Using smart phones for deformations measurements of structures - El-Ashmawy, Khalid L. A. (Geodesy and Cartography, 2017)
The present work tests the suitability of using the digital cameras of smart phones for close range photogrammetry applications. For this purpose two cameras of smart phones Lumia 535 and Lumia 950 XL were used. The resolutions of the two cameras are 5 and 20 Mpixels respectively. The tests consist of (a) self calibration of the two cameras, (b) the implementation of close-range photogrammetry using the cameras of the two smart phones, theodolite intersection with LST method, and linear variable displacement transducers (LVDTs) for the measurement of vertical deflections, and (c) accuracy of photogrammetric determination of object space coordinates. The results of using Lumia 950 XL are much better than using Lumia 535 and are better or comparable to the results of theodolite intersection with least squares technique (LST). Finally, it can be stated that the digital cameras of smart phones are suitable for close range photogrammetry applications according to accuracy, costs and flexibility.